2018
DOI: 10.1002/adem.201800255
|View full text |Cite
|
Sign up to set email alerts
|

Clustering in Age‐Hardenable Aluminum Alloys

Abstract: This review gives an overview of the effects of clusters in various aluminum alloys. Characterization methods are discussed in general and results for the important AlMgSi alloys are presented in detail. Indirect characterization methods, such as hardness, tensile testing, electrical resistivity, differential scanning calorimetry, and positron annihilation spectroscopy are discussed, as well as atom probe tomography for the direct measurement of clusters. A particular focus is set on atom probe tomography, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 140 publications
(274 reference statements)
0
37
0
Order By: Relevance
“…maximum separation or other related). When affected by trajectory aberrations, the identification of clusters based on a threshold of distance or composition [3] is hence likely to fail to assess which atoms physically belong to clusters. While several studies have investigated the effect of an imperfect reconstruction (by adding random Gaussian noise to a synthetic APT volume) on cluster identification methods, most concluded that it did not yield too strong an effect on the clusters on the basis of a strongly underestimated effective spatial The values that we report here seem to correspond to the worst case scenario of these studies, when problems start to arise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…maximum separation or other related). When affected by trajectory aberrations, the identification of clusters based on a threshold of distance or composition [3] is hence likely to fail to assess which atoms physically belong to clusters. While several studies have investigated the effect of an imperfect reconstruction (by adding random Gaussian noise to a synthetic APT volume) on cluster identification methods, most concluded that it did not yield too strong an effect on the clusters on the basis of a strongly underestimated effective spatial The values that we report here seem to correspond to the worst case scenario of these studies, when problems start to arise.…”
Section: Discussionmentioning
confidence: 99%
“…precipitates, in the nanometer-size range and below [1,2]. This is particularly true for solute clusters [3]. The detailed analysis of the composition of these precipitates and clusters is of high relevance to studies of the early stages of nucleation of new phases, which control both the physical properties of materials and the further evolution of the microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…This could be explained by the clusters formed upon pre-ageing, which may stabilize the dislocations structure via coherency strengthening effects [34], and thus restrain recovery. The clusters formed upon pre-ageing represent greater obstacles to dislocations than those formed upon natural ageing, and, more importantly, they are stable and hardly dissolve upon artificial ageing [35].…”
Section: Resultsmentioning
confidence: 99%
“…In EN-AW-6061, the effect of 100 at.-ppm of Sn vanishes when air cooling is applied (Figure 3b). Note that the higher Si-content in EN-AW-6016 may lead to a significant acceleration of natural aging in general [16,23,29].…”
Section: Discussionmentioning
confidence: 99%
“…The crucial property of clusters, in terms of transformation in the course of AA, is claimed to be the Mg/Si ratio. While measurements show a balanced ratio of about one for PA-treatments, clusters tend to follow the overall composition of the alloy after NA [12,13,14,15,16]. Besides “conventional” pre-aging for several hours, applying a spike as a short-term treatment at high temperatures (180 °C and 200 °C) also shows promising results [6,17,18].…”
Section: Introductionmentioning
confidence: 99%